O protagonismo do poder público na condominização residencial da cidade de Alfenas-MG - Lilian Mara de Castro Azevedo; Evânio dos Santos Braquinho (Confins)
This paper proposes a discussion about the role of urban space producing agents in the phenomenon of the proliferation of closed residential condominiums in the city of Alfenas, State of Minas Gerais, starting in 2010. The main objective is to analyze the relationships that made possible the implementation of these enterprises, dialoguing with the transforming agents of the city and the consumption relations of urban space. In addition to the theoretical reference, interviews were carried out with representatives of municipal public authorities and real estate developers. The analyzes indicate a strong interference of the State in the production of this fragmented urban space, evidencing a mercantile strategy not highlighted in the approaches on this theme. This article presents as an essay in the sense of relating a previous work to the political analysis of urban planning and the role of the State as a space producer, which are part of our research project of the Master's Degree in Geography at Universidade Federal de Alfenas-MG.